2019
DOI: 10.1101/586784
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

3D microenvironment stiffness regulates tumor spheroid growth and mechanics via p21 and ROCK

Abstract: Mechanical properties of cancer cells and their microenvironment contribute to breast cancer progression. While mechanosensing has been extensively studied using twodimensional (2D) substrates, much less is known about it in a physiologically more relevant 3D context. Here we demonstrate that breast cancer tumor spheroids, growing in 3D polyethylene glycol-heparin hydrogels, are sensitive to their environment stiffness. During tumor spheroid growth, compressive stresses of up to 2 kPa built up, as quantitated … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 64 publications
(34 reference statements)
1
18
0
Order By: Relevance
“…It is known that compressive stresses will prevent spheroid growth due to volume constraints, an effect observed with various spheroid and scaffold types. [ 81–84 ] We observed the most limited growth in porcine GelMA polymerized at 4 °C, where we also observed the scaffold radially shrinking over time. Acellular porcine GelMA with high DS polymerized at 4 °C in a well plate exhibited a 28.7 ± 2.1% decrease in scaffold diameter 3 days after crosslinking.…”
Section: Resultsmentioning
confidence: 66%
See 1 more Smart Citation
“…It is known that compressive stresses will prevent spheroid growth due to volume constraints, an effect observed with various spheroid and scaffold types. [ 81–84 ] We observed the most limited growth in porcine GelMA polymerized at 4 °C, where we also observed the scaffold radially shrinking over time. Acellular porcine GelMA with high DS polymerized at 4 °C in a well plate exhibited a 28.7 ± 2.1% decrease in scaffold diameter 3 days after crosslinking.…”
Section: Resultsmentioning
confidence: 66%
“…highlights that supplementing GelMA scaffolds with fibrous collagen is required for MDAMB231 spheroid invasion into scaffolds with storage moduli ( G ′) higher than the optimal window identified herein. [ 84 ] Spheroid invasion was observed in composite GelMA‐collagen scaffolds with storage moduli ( G ′) as high as 12 kPa. This suggests spheroid invasion may be possible in GelMA scaffolds with coordinated physical gelation and chemical crosslinks upon supplementing the matrix with fibrous support materials, such as collagen.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, mechanical confinement or external pressure have been shown to hamper cell proliferation in tumor spheroids. [ 14–18 ] Thus, it has been hypothesized that the actin cortex of cancer cells exhibits oncogenic adaptations that allow for ongoing mitotic rounding and division inside tumors. [ 19 ] In fact, it was shown that the human oncogene Ect2 contributes to mitotic rounding through RhoA activation [ 7,10 ] and that Ras overexpression promotes mitotic rounding.…”
Section: Introductionmentioning
confidence: 99%
“…PAAm microgel beads have shown the potential to mimic cells with respect to their diameter and elasticity, and to allow for a comparison between different mechanical assessment techniques, such as atomic force microscopy (AFM) and real-time deformability cytometry (RT-DC). 91 Due to their mechanical similarities to cells, PAAm beads have been used as stress sensors, [91][92][93] for the calibration of RT-DC measurements, 94 and to build 3D colloidal scaffolds with spatially differing mechanical layers for cell growth, migration and mechanosensitivity studies. 95 Here, we investigate the mechanical properties of hydrogels containing PAAm microgel beads and embryo mouse fibroblast (NIH/ 3T3) cells for small and large deformations under compression, tension, and torsional shear loadings.…”
Section: Introductionmentioning
confidence: 99%